Resilience and Transformation: Analyzing the Success of Crypto Exchanges Post-Pandemic and Global Conflict Using the DeLone & McLean Model - Mohamad Nasoha (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
The purpose of this research is to analyze the success of digital currency using DeLone and McLean Model, which include some factors such as system quality, information quality, service quality, user satisfaction, and intention to continue using platform. This research focus on crypto exchanges, such as Binance, Coinbase Exchange, and Kraken and the impact of Covid Pandemic on crypto markets. The data was taken from CoinMarketCap during  2018  to 2024, and focus on the ten largest digital currencies based on market capitalization. The result shows that market capitalization and trading volume of crypto currencies increased significantly during 2018 to 2024. Although there was decrease in 2022  because of global economy instability which was triggered by Rusia - Ukraine war.  BTC and ETH were still dominating market,  while the new coins such SOL and AVAX showed rapid growth. The factors such as system quality, information quality, and service quality really influenced on user satisfaction and also the intention to continue using crypto exchanges platform. Beside increasing  volatility of crypto markets, Covid Pandemy caused acceleration of digital asset adaption. Tis research concluded that crypto markets has significant resilience on global economy turmoil with the strong recovery in 2023 to 2024.